DIVERSITY OF MAMMAL TYPES IN THE GHIMBE PERAMUNAN TRADITIONAL FOREST AREA, PENANDINGAN VILLAGE, SEMENDE TANARA LAUT DISTRICT, MUARA ENIM DISTRICT - Helida, Asvic; Al Azmi, Ridho; Lensari, S.Hut, M.Si, Delfy (Universitas Muhammadiyah Palembang, 2023)
Mammals are one of the classes in the Animalia kingdom which have several features both in terms of physiology, nervous system and level of intelligence so that these taxa have a wide distribution. There is no data on the diversity of wild animal species, especially mammals in the Ghimbe Peramunan Traditional Forest area, so it needs attention from various parties such as the local community and the local government. This research was carried out to determine the diversity and evenness of mammal species in the Ghimbe Peramunan Traditional Forest area. This research was carried out in Penyandingan Village, Semende Darat Laut District, Muara Enim Regency in September 2022. The research method used was Quantitative Descriptive. The data collection method used was sampling using the strip transect method using straight lines and the width of the path as boundaries and interviews with traditional leaders, managers and residents around the customary forest. The types of mammals found in this study consisted of Callosciurus notatus, Paradoxurus hermaphroditus, Symphalangus syndactylus, Sus scrofa, Presbytis melalophos, Macaca fascicularis, Rattus argentiventer, Nycticebus coucang, and Helarctos malayanus. The results of research data in the Ghimbe Peramunan Traditional Forest Area, the value of species diversity (H') was 0.584 (low species diversity). Meanwhile, the type evenness value (E) is 0.266 (low type evenness). The number of mammal species found directly and in traces was smaller compared to the results of interviews. The large number of human activities that occur in the area are thought to have an influence on the existence and activities of animals in the area, so that animals are not easy to find directly